Analysis of Green Accounting as Accountability of Hospitals: Analisis Green Accounting sebagai Tanggung Jawab Rumah Sakit - Muhammad Mualiyin; Hadiah Fitriyah (Academia Open, 2023)
General Background the growing concern for environmental sustainability has prompted organizations, including healthcare institutions, to adopt green accounting practices. Specific Background this study employs a literature review approach to examine the application of green accounting at a specific hospital, aiming to identify relevant theoretical references and documentation. Knowledge Gap despite the significance of green accounting in enhancing accountability and transparency in financial reporting, there remains a lack of comprehensive understanding and implementation among healthcare institutions, particularly in the context of this hospital. Aims the study aims to analyze the current state of financial reporting based on green accounting, assess the application of green accounting principles, and evaluate the implementation of environmental prevention costs at the hospital. Results findings indicate that while the hospital has integrated environmental costs into general and administrative expenses, detailed green accounting reports are lacking. Additionally, staff awareness and understanding of green accounting principles remain insufficient, and the implementation of environmental prevention costs has not yet been realized. Novelty this study contributes to the literature by providing empirical insights into the application of green accounting in a healthcare setting, highlighting the need for improved practices. Implications the findings underscore the importance of enhancing knowledge and practices of green accounting within healthcare organizations to foster greater environmental accountability and sustainability. Highlights : Integration of environmental costs into financial reporting is observed. Lack of detailed green accounting reports hinders transparency. Insufficient staff awareness of green accounting principles limits effectiveness. Keywords : Green Accounting, Environmental Costs, Healthcare, Accountability, Financial Reporting